Occurrence of Clinical Options of Undifferentiated Connective Tissue Dysplasia in Uzbek Population - Gulandon Zikrievna, Shodikulova; Zarrina Bakhtiyarovna, Babamuradova (International Journal of Psychosocial Rehabilitation, 2020)
Object: To study the occurrence of clinical variants of undifferentiated connective tissue dysplasia (NDST) in the Uzbek population. Methods: 105 individuals were examined, including 49 (46.4%) males and 56 (53.6%) females aged 15 to 28 (20.13 ± 0.66) years with signs of NDCT. Findings: The incidence of NDCT in women is within 40%, in males 66.0%. An analysis of the distribution of NDST by place of residence showed a slight predominance of city residents (60 patients lived in the city, 45 in the countryside); an increase in the frequency of HLA gene class II was observed: HLA DRB1 *, DQA1 * 04: 01, and DQB1 * 04: 01/2. The incidence of clinical options is joint hypermobility (100%), changes in the shape of the spine (44%), chest (43.8%), skin extensibility of varying severity (38.8%), small developmental anomalies (21.1%), and flat feet (20.4%). The frequency of combinations of external hair dryers: a combination of 6 revealedat 5 (4,5%), 5-th at 11 (10%), 4-th at 21 (20%), 3-rd at 26 (24,3%), 2-nd at 31 (30,6%) examined Conclusions: Thus, the early detection of signs of NDCT in young people among the Uzbek population will optimize early diagnosis and predict the outcome of the disease.